Lo studio «disinteressato» come nuovo terreno applicativo della scienza dell’educazione - La Porta, Lelio (International Gramsci Journal, 2023)
Cultural anthropology, educational science and philosophy are closely connected. Can this close connection find practical application ? This essay will try to answer the question in Gramscian terms, by taking into consideration the methodological approach suggested by Gramsci, with the concept of “disinterested study”, applying it the scholastic field, that is the relation of supremacy-direction to subordination that is established between teacher and learner. The starting point and laboratory is the Italian school, that is the real place in which the method of disinterested study is applied. The protagonists are the teacher (meaning anyone who is teaching), on one side, and the pupil on the other. The teacher must possess the ability to lead, while the pupil is required to study and carry out research, in addition to having the discipline and scientific accuracy necessary in order to overcome his initially subordinate situation. This new relationship between teacher and learner may allow the real and true anthropological Gramscian option to be realized: namely through the work which results from the uprooting of situation of subordination, it is possible to arrive to the progressive rooting of a situation in which critical self-awareness is undertaken, thereby arriving at full autonomy.